MAPPING OF CONSERVATION AREA PLAN IN NORTH POLOMBANGKENG DISTRICT, TAKALAR REGENCY - Nurul Fajeriana; Muhammad Arifin Abd Kadir (Universitas Medan Area, 2020)
North Polombangkeng District is one of the districts in Takalar Regency, South Sulawesi, where 44% of the total land area of 9495 ha out of 21225 ha are steeply sloped areas. Therefore we need a policy direction on the arrangement of the use of conservation areas to support the sustainability of the existing environment in the form of mapping conservation area plans. This study uses a soil survey method and evaluation of land capability. Physical Factors the environment is a limiting factor in determining land use policy, namely slope factors, soil sensitivity to erosion, and rainfall intensity. The research shows that Barugayya Village, Towata Village, and Kampung Baru Village are included in class IV land grade classification and Ko'mara Village in Class VI. At the same time, the Scoring Assessment of Physical Environmental Factors in Forest Areas has a range of values ranging from 160 to 215, the area of which is planned to be a conservation area. Determination of Conservation Area refers to the function criteria of forest area based on the scoring System of the Minister of Agriculture Regulation in Minister of Agriculture Decree No. 837/Kits/Um/11/80.